2019
DOI: 10.4317/jced.55739
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of frictional forces during the closure of extraction spaces in passive self-ligating brackets and conventionally ligated brackets using the finite element method

Abstract: Background This study compared the frictional force resulting from the bracket/archwire interface and the stress at the root/periodontal ligament/bone interface, between passive self-ligating brackets and conventionally ligated brackets, during the space closure stage. Material and Methods A cone beam tomography was taken to a female patient that required extraction of upper first premolars and passive self-ligating system; three months after its activation, a cone beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
2
0
4
Order By: Relevance
“…In this study, the results of the frictional force generated during the alignment and leveling stage were similar with 3M® SmartClip passive self-ligating brackets and conventional brackets, with Leone® Slide low-friction ligatures, in all combinations of archwires, and frictional forces of 0.50MPa and 0.64MPa, respectively. These findings are similar to those found in a previous study (5), where the same bracket/ligation systems showed the same frictional force behavior during the displacement of 0.019x0.025” steel archwires. One possible explanation for this physical behavior is that the SmartClip brackets were provided with a regular force in all the archwire configurations employed by the NiTi active clips.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the results of the frictional force generated during the alignment and leveling stage were similar with 3M® SmartClip passive self-ligating brackets and conventional brackets, with Leone® Slide low-friction ligatures, in all combinations of archwires, and frictional forces of 0.50MPa and 0.64MPa, respectively. These findings are similar to those found in a previous study (5), where the same bracket/ligation systems showed the same frictional force behavior during the displacement of 0.019x0.025” steel archwires. One possible explanation for this physical behavior is that the SmartClip brackets were provided with a regular force in all the archwire configurations employed by the NiTi active clips.…”
Section: Discussionsupporting
confidence: 91%
“…High levels of frictional force between the slot and the archwire may cause binding of these two components, which would result in a shallow (if any) dental movement. Slight forces are deemed as optimum during orthodontic treatment because they maintain anchorage, allow more significant dental movement, and decrease radicular reabsorption risks (3-5).…”
Section: Introductionmentioning
confidence: 99%
“…Por lo tanto, se puede decir que visto con MEF, un mayor calibre de alambre (0,019" x 0,025"), no es igual a mayor área de contacto entre bracket y alambre, siendo esto último un factor determinante en la resistencia friccional resultante del sistema ortodóncico (Figura 4). En este sentido, diversos autores (23-26), a partir de pruebas de deslizamiento "in vitro," y usando diferentes combinaciones de alambres y brackets, han logrado probar que donde existe una mayor área de contacto entre el bracket y el alambre, existe una mayor zona para el desarrollo de fenómenos asociados con la fricción como "stick slip" (5,11), que se refiere al aumento de la resistencia friccional debido al bloqueo mecánico entre las rugosidades de dos superficies en contacto durante el deslizamiento. En contraste, Voudourisa y colaboradores ( 27) reportaron que el tamaño del alambre asociado con mayor fricción fue el calibre 0,019" x 0,025", seguido por los alambres 0,018" x 0,018" y 0,020", enfatizando la indicación de los alambres redondos para biomecánica de deslizamiento de autoligado.…”
Section: Discussionunclassified
“…De esta manera, se validó el FEM para estudiar fuerzas friccionales en diferentes combinaciones de brackets y arcos. Las propiedades mecánicas de los brackets y alambres tenidas en cuenta en el modelo fueron 205 y 190 GPa, 200 y 193 MPa, y 0,31 y 0,3 (Poisson's Ratio), respectivamente (10,11).…”
Section: Odontologíaunclassified
“…The limitations of this study include the limitations of the FEM; this model is a numerical method that can present numerical and geometric approximation errors. Homogeneous and continuous materials are assumed, in addition, the edge and load conditions try to reproduce the real phenomenon, therefore, clinical validation becomes relevant; however, the results cannot be extrapolated to all patients due to anatomical variation between them, but it allows an exact approach to the behavior of the real phenomenon, which can be complemented by clinical studies (28,29).…”
Section: Discussionmentioning
confidence: 99%